Sociodemographic and behavioral characteristics of older people with HIV in Almaty City, Kazakhstan: A cross-sectional study - Nursultan Nurzhigitov; Deborah Gustafson; Zhamilya Nugmanova; Alfiya Denebayeva; Aigerim Alimbekova; Gulnara Nugumanova; Gulmira Kalzhanbayeva; Ademi Sarsembiyeva; Jack DeHovitz (PLoS ONE, 2025)
Introduction Globally, there are increasing numbers of people with HIV (PWH) age ≥ 40 years (y). Despite this, there are few studies of older PWH in low- and middle-income countries, and no studies in Kazakhstan. Aging with HIV influences HIV treatment response and is associated with the occurrence of non-communicable diseases. Methods and materials A cross-sectional study of PWH ≥ 40y was conducted at the Almaty City AIDS Center in Kazakhstan. Biological, sociodemographic, health behavior, medical history, mental and cognitive health, quality of life, and HIV factors were measured and characterized. Results The study enrolled and interviewed a clinical sample of 150 PWH ≥ 40y. Males (sex at birth) comprised 54.7% (N = 82); average age 51.6y, + /-10.4y; 54.7% aged 40-49y; maximum age 75y. Females (sex at birth) were younger (47.5y) than males (56.8y) (p = 0.020). Level of education differed by sex (p = 0.001). Females with HIV were more likely than males to be unemployed (33.8% versus 24.5%, respectively, p < 0.001). Among all PWH, 4% were disabled, 8.7% retired, 37.3% were in an official or civil marriage and 60.7% lived in their own home. More males consumed alcohol than females (32.9% versus 1.3%, respectively) (p = 0.001). Drug use was higher among males (25.6%) compared to females (8.8%) (p = 0.050); 91.4% of males versus 64.7% of females smoked ≥100 cigarettes in their lifetime, and 76.8% of males versus 48.5% of females smoked cigarettes currently (p = 0.001). HIV viral load among males was higher (p = 0.050) and CD4 + count, lower among males (p = 0.004) compared to females. Physical and physiological health, environmental and social relationships among males and females were similar. Conclusions The majority of PWH were of working age, employed, and reported good quality of life, however, sex differences were observed. Future prospective studies are recommended.